Moyamoya Disease with Intraventricular Hemorrhage in a Child: A Case Report - Regmi, Nisha; Shrestha, Bibek; Karn, Vivek; Regmi, Pradeep Raj (Journal of Institute of Medicine Nepal, 2025)
Moyamoya disease is a rare progressive cerebrovascular disorder in Nepal characterized by stenosis or occlusion of cerebral arteries with abnormal collateral vessels, and hemorrhagic presentation in children is extremely uncommon. We report an 8-year-old girl with intraventricular hemorrhage presenting with seizures, vomiting, and decreased consciousness. Imaging revealed characteristic angiographic features of Moyamoya disease. She was managed with external ventricular drainage and supportive treatment, achieving significant recovery. This case highlights the importance of considering Moyamoya disease in pediatric hemorrhagic stroke and underscores the need for early imaging and timely intervention.